Impact of irrigation in the command area of Bagmati Irrigation Project - Dahal, Ananta Raj (Economic Journal of Development Issues, 2015)
As an agrarian economy Nepal, irrigation is most important to achieve economic development. This research analyzes the impact of Bagmati irrigation project (BIP) in the command area. A comparative study of the output, employment, income and other variables related to the irrigated and un-irrigated agricultural land within and outside the Bagmati irrigation project area has led to positive result. This study found that agricultural productivity increases from 19.32 percent to 102.78 percent in different crops. Likewise irrigation seems to have contributed to increase employment, investment, net income. DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11854 Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 1-14